LOW MISSING MASS, SINGLE- AND DOUBLE DIFFRACTION DISSOCIATION AT THE LHC - Jenkovszky, L.; Salii, A.; Turoci, J.; Himics, D. (Одеські астрономічні публікації, 2012)
Low missing mass, single- and double diffraction dissociation is calculated for the LHC energies from a dual-Regge model. The model reproduces the rich resonance structure at low mass region, and approximate behavior for high mass-region.